If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6y + -5 = 13 Reorder the terms: -5 + -6y = 13 Solving -5 + -6y = 13 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -6y = 13 + 5 Combine like terms: -5 + 5 = 0 0 + -6y = 13 + 5 -6y = 13 + 5 Combine like terms: 13 + 5 = 18 -6y = 18 Divide each side by '-6'. y = -3 Simplifying y = -3
| 6a+12=66 | | 3x+y= -12 | | 6x-7=331 | | 4(2x+4)-2(x-2)=4(x-2) | | 2x^2+288=0 | | 6n+2(4n+5)= | | y=x^2+15x+56 | | X*6+80=X*13+11 | | 210x-68=56x+1164 | | 8b-7+3b=19-2b | | n-31=-35 | | 2x+6x-18=150 | | 9n-2-3m=8-4m | | 5*-32= | | x^3-x+6=0 | | 7(8b+12)=700 | | 9s-11=31s | | 7x-5=7x+6 | | x^2+10x-4= | | x^3+x^2+13x+4=0 | | 2x+6(x-3)=150 | | 46=-9x+10 | | 12x+8=-8+13x | | 4(3b+5)=104 | | 0.3x+12.9=4.6x | | 4x-25x= | | 8x-20=4-11 | | -(2x-x)=0 | | 9x-15=3x-3 | | 3b-6+6b=43+2b | | 6(7x+7)=336 | | -3x+10=10-3x |